Feasibility of using dried blood spots for HIV viral load testing among HIV‐infected individuals in Thailand using QIAGEN QIAsymphony‐artus HIV‐1 platform. Issue 9 (1st June 2019) - Thepbundit, Viraporn; Ngo‐Giang‐Huong, Nicole; Salvadori, Nicolas; Laolue, Auswin; Kunyanone, Naowarat; Sata‐un, Jaggrit; Jourdain, Gonzague; Sirirungsi, Wasna; Khamduang, Woottichai
Abstract: In settings where plasma preparation and sample centralization are not feasible or inconvenient, dried blood spots (DBS) could be used as an alternative specimen to plasma to assess antiretroviral treatment response among HIV‐infected individuals. This study was aimed to (1) validate the recent QIAsymphony‐ artus assay for DBS HIV viral load (VL) and (2) assess the feasibility of measuring HIV VL on DBS using this assay in Thailand. Ethylenediaminetetraacetic acid‐blood samples from 99 HIV‐infected individuals were used to prepare paired DBS and plasma. Also, DBS samples were shipped to three distant hospitals in the northern region. After short‐term storage, DBS were returned by regular post to the AMS laboratory and were re‐tested for HIV VL using the same platform. HIV VL results were compared using Pearson's correlation and Bland‐Altman analysis. DBS HIV VL fairly correlated to plasma HIV VL (R = 0.62) with a mean difference of 0.02 log10 IU/mL (SD = 1.06). A high correlation (R = 0.79) was observed between HIV VL in DBS before and after shipping (mean difference = 0.14 log10 IU/mL, SD = 0.74), indicating good stability of HIV RNA in DBS. DBS can be used as an alternative specimen for HIV VL monitoring in Thailand. However, measurement of HIV VL with the QIAGEN QIAsymphony ‐artus assay should be improved, especially the DBS pre‐extraction process. Highlight: This study provides the performance analysis of the QIAGEN QIAsymphony‐artus HIV‐1 for the measurement of HIV‐1 viral load (VL) on dried blood spots (DBS) and after DBS shipment in real conditions in Thailand. The assay demonstrated comparable performance on plasma HIV‐1 VL testing to that obtained from the reference assay. Although a fair correlation between plasma and DBS HIV‐1 VL was observed when using this platform, however, HIV RNA is quite stable in DBS up to 4 days of shipping by regular post in conditions of high temperature and humidity.